Analisis kepuasan pernikahan pada pasangan usia dini - Nahdalia, Neka; Afdal, Afdal (Universitas Negeri Padang, 2023)
Early marriage is a marriage carried out by teenagers aged 15 to 20 years, and there is no readiness to marry. Satisfaction in marriage is very important, because the fulfillment of household relations will be more harmonious. This study aims to determine marital satisfaction in early age couples. This research is a qualitative research using a case study approach. The subjects in this study were 5 couples who married at an early age, 3 of them married because of their own desires and 2 couples married because they were pregnant out of wedlock, as well as 5 informants. The instruments in this study were interview guides and documentation, while the analysis of the data that had been obtained from the interviews was then used as a transcript, and given a theme as a result of the findings and after that, the data was interpreted. The results showed that marital satisfaction was only found in sexual satisfaction, whereas in the communication aspect one group of subjects was found to be satisfied, because communication in the household of subject group 1 went well and understood each other, while in the aspect of joint activities, religion, problem solving and financial satisfaction were not found. Marital satisfaction is very important in a husband and wife relationship in order to create a harmonious relationship and early marriage does not guarantee marital satisfaction and happiness, so it is suggested that couples who want to get married should reconsider, so that unwanted households do not occur.